Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the given problem, let's start by analyzing the logarithmic equation [tex]\(\log_3(x + 5) = 2\)[/tex]. Our goal is to find an equivalent equation in a different form.
Step-by-step:
1. Understanding the Logarithmic Equation:
The given equation is [tex]\(\log_3(x + 5) = 2\)[/tex]. A logarithm is the inverse of an exponentiation. Specifically, [tex]\(\log_b(a) = c\)[/tex] means that the base [tex]\(b\)[/tex] raised to the power of [tex]\(c\)[/tex] equals [tex]\(a\)[/tex].
2. Convert to Exponential Form:
The equation [tex]\(\log_3(x + 5) = 2\)[/tex] can be rewritten in its exponential form as follows:
[tex]\[ 3^2 = x + 5 \][/tex]
This step uses the property that if [tex]\(\log_b(a) = c\)[/tex], then [tex]\(b^c = a\)[/tex].
3. Rewrite the Equation:
Simplify [tex]\(3^2\)[/tex]. We know that:
[tex]\[ 3^2 = 9 \][/tex]
Hence, the equation [tex]\(3^2 = x + 5\)[/tex] simplifies to:
[tex]\[ 9 = x + 5 \][/tex]
4. Shifting Terms:
To isolate [tex]\(x\)[/tex], we subtract 5 from both sides of the equation:
[tex]\[ 9 - 5 = x \][/tex]
Simplifying further gives:
[tex]\[ 4 = x \][/tex]
Among the provided options, the equivalent equation to [tex]\(\log_3(x + 5) = 2\)[/tex] is:
[tex]\[ 3^2 = x + 5 \][/tex]
Therefore, the correct answer is:
[tex]\[ 3^2 = x + 5 \][/tex]
Step-by-step:
1. Understanding the Logarithmic Equation:
The given equation is [tex]\(\log_3(x + 5) = 2\)[/tex]. A logarithm is the inverse of an exponentiation. Specifically, [tex]\(\log_b(a) = c\)[/tex] means that the base [tex]\(b\)[/tex] raised to the power of [tex]\(c\)[/tex] equals [tex]\(a\)[/tex].
2. Convert to Exponential Form:
The equation [tex]\(\log_3(x + 5) = 2\)[/tex] can be rewritten in its exponential form as follows:
[tex]\[ 3^2 = x + 5 \][/tex]
This step uses the property that if [tex]\(\log_b(a) = c\)[/tex], then [tex]\(b^c = a\)[/tex].
3. Rewrite the Equation:
Simplify [tex]\(3^2\)[/tex]. We know that:
[tex]\[ 3^2 = 9 \][/tex]
Hence, the equation [tex]\(3^2 = x + 5\)[/tex] simplifies to:
[tex]\[ 9 = x + 5 \][/tex]
4. Shifting Terms:
To isolate [tex]\(x\)[/tex], we subtract 5 from both sides of the equation:
[tex]\[ 9 - 5 = x \][/tex]
Simplifying further gives:
[tex]\[ 4 = x \][/tex]
Among the provided options, the equivalent equation to [tex]\(\log_3(x + 5) = 2\)[/tex] is:
[tex]\[ 3^2 = x + 5 \][/tex]
Therefore, the correct answer is:
[tex]\[ 3^2 = x + 5 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.